Progress in active devices for optical fiber communication - Qiming WANG; Lingjuan ZHAO; Hongliang ZHU; Qin HAN; Buwen CHENG (Dianxin kexue)
The rapid progress of optical fiber communication makes it become the key technology for the information society.The active and passive optoelectronic devices are the foundation of the optical communication.The progress and development trend of the key active optoelectronic devices were reviewed,including DFB laser,photonic integrated circuit,980 nm high power laser for EDFA pumping,compound semiconductor photodetector and Si-based long wavelength photodetector.